Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s12041-015-0561-6
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs: emerging players in gene regulation and disease pathogenesis

Abstract: The advent of next-generation sequencing has demonstrated that eukaryotic genomes are extremely complex than what were previously thought. Recent studies revealed that in addition to protein-coding genes, nonprotein-coding genes have allocated a large fraction of the genome. Long noncoding RNA (lncRNA) genes are classified as nonprotein-coding genes, serving as a molecular signal, decoy, guide and scaffold. They were suggested to play important roles in chromatin states, epigenetic and posttranscriptional regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 88 publications
1
60
0
Order By: Relevance
“…Yet, origins of lncRNAs are not well understood so far. Due to the fact that lncRNAs harbor low sequence conservations and rapid evolution among mammals, several evolutionary hypotheses could be proposed such as: (1) lncRNAs might be generated by the metamorphosis of protein-coding genes through a gene duplication process; (2) lncRNAs might have evolved from segmental or whole gene duplication of other ncRNA genes; (3) lncRNAs might have originated via de novo generation, such as alternations in genomes including chromosomal rearrangement, generation of splice sites and promoters might transform nonfunctional genomic sequences to functional lncRNAs; and (4) transposable elements (TEs) insertions might be another origin of lncRNAs (Ponting et al, 2009; Kaessmann, 2010; Kapusta et al, 2013; Kazemzadeh et al, 2015). However, it was observed that rarely or only a minority (~15%) of lncRNAs showed significant sequence similarity to other lncRNAs or protein-coding genes on positions other than the shared repetitive elements, suggesting that novel lncRNAs genes are basically originated rather from de novo non-exonic sequences and/or from TEs than duplication (Derrien et al, 2012; Kapusta et al, 2013).…”
Section: Characters and Functions Of Lncrnasmentioning
confidence: 99%
“…Yet, origins of lncRNAs are not well understood so far. Due to the fact that lncRNAs harbor low sequence conservations and rapid evolution among mammals, several evolutionary hypotheses could be proposed such as: (1) lncRNAs might be generated by the metamorphosis of protein-coding genes through a gene duplication process; (2) lncRNAs might have evolved from segmental or whole gene duplication of other ncRNA genes; (3) lncRNAs might have originated via de novo generation, such as alternations in genomes including chromosomal rearrangement, generation of splice sites and promoters might transform nonfunctional genomic sequences to functional lncRNAs; and (4) transposable elements (TEs) insertions might be another origin of lncRNAs (Ponting et al, 2009; Kaessmann, 2010; Kapusta et al, 2013; Kazemzadeh et al, 2015). However, it was observed that rarely or only a minority (~15%) of lncRNAs showed significant sequence similarity to other lncRNAs or protein-coding genes on positions other than the shared repetitive elements, suggesting that novel lncRNAs genes are basically originated rather from de novo non-exonic sequences and/or from TEs than duplication (Derrien et al, 2012; Kapusta et al, 2013).…”
Section: Characters and Functions Of Lncrnasmentioning
confidence: 99%
“…Therefore, a better understanding of the pathogenesis and progression of RCC will require new therapies with improved outcomes. After miRNAs, lncRNAs have recently been implicated in many human disorders for their regulator roles; the dysregulation of lncRNAs serves as a causal factor in tumorigenesis and the progression of cancers [20] . As emerging stars in gene regulation, epigenetics, and human disease, lncRNAs have attracted much attention from researchers searching for the pathogenesis and best treatments for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Based on proximal protein-coding mRNAs, lncRNAs have been classified as sense lncRNAs, antisense lncRNAs, intronic lncRNAs, bidirectional lncRNAs, and long intergenic ncRNAs (lincRNAs). LncRNAs have been shown to affect every stage of a gene's life cycle, including chromosome reconstruction, transcription, post-transcription, and intracellular metabolism [15][16][17][18]. In a recent study, the role of lncRNAs in the development of autoimmune diseases was highlighted [19].…”
Section: Introductionmentioning
confidence: 99%